1986
DOI: 10.1177/0022002186017004006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation of A Developmental Test (Dial-R) for Young Children in Taiwan

Abstract: DIAL-R (Developmental Indicators for the Assessment of Learning-Revised), a developmental test for children 2 to 6 years old, was modified minimally and translated for use in Taiwan. After it was normed on a stratified sample of 322 children in Taipei, analyses of internal consistency, construct validity, test-retest reliability, and concurrent validity all indicated that the test meets the standards of a technically adequate screening test for that culture, giving it criterion-referenced meaning. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…These results may be explained by the fact that in Ethiopia, as opposed to other Western societies, no emphasis is put on visual motor organization, which was examined in the current and previous studies (Katz et al, 2002;Rosenblum et al, 1997Rosenblum et al, , 2000. In fact, visual motor and spatial organization skills are acquired through practice of drawing or writing tasks, while proceeding through formal education and beginning from a young age (Mardell-Czudnowski et al, 1986;Saeki et al, 1995). Most youths who participated in this study had not received formal education in Ethiopia and lacked elementary experience in drawing or writing tasks.…”
Section: Similarity Between Groupsmentioning
confidence: 64%
“…These results may be explained by the fact that in Ethiopia, as opposed to other Western societies, no emphasis is put on visual motor organization, which was examined in the current and previous studies (Katz et al, 2002;Rosenblum et al, 1997Rosenblum et al, , 2000. In fact, visual motor and spatial organization skills are acquired through practice of drawing or writing tasks, while proceeding through formal education and beginning from a young age (Mardell-Czudnowski et al, 1986;Saeki et al, 1995). Most youths who participated in this study had not received formal education in Ethiopia and lacked elementary experience in drawing or writing tasks.…”
Section: Similarity Between Groupsmentioning
confidence: 64%
“…Cross-cultural studies have emphasized the danger of applying a standardized test developed in one culture as a diagnostic instrument for individuals from a different culture (Berry, Poortinga, Segall, & Dasen, 1992;Cella, Lloyd, & Wright, 1996;Mardell-Czudnowski, Hwang, & Wang, 1987;Martin, Sewell, & Manni, 1977;Poortinga, 1989;Poortinga, Fons, & Vijver, 1987;Wilson, 1994). Such an external comparison may not be valid because tests of ability and achievement are developed within a context-specific environment with culturally specific content (Miller-joanes, 1987).…”
mentioning
confidence: 99%
“…Comparative studies have already shown that different developmental rates exist among children with different cultural backgrounds. The differences are not only found in the development of the component skills that underlie visual-motor integration such as visual perception, fine motor coordination, and cognitive concept development, but also in visualmotor integration itself (Bryant, Davies, & Newcombe, 1974;Liu, 1972;Mao, 1995;Mardell-Czudnowski, et al, 1987;Martin, et al, 1977;Saeki, Clark, & Azen, 1985;Schooler & Anderson, 1979;Solomons & Solomons, 1975;Song & Ginsburg, 1987;Stevenson, Stigler, Lucker, Lee, Hsu, & Kitamura, 1985).…”
mentioning
confidence: 99%
“…Familial and environmental factors also include cultural background. Culture and religious beliefs are related to familial attitudes toward the child, create expectations from the child, and encourage the development of specific behaviors and skills (14,(18)(19)(20)(21). All of these may affect the child's participation (22).…”
Section: Introductionmentioning
confidence: 99%